Membangun Generasi Berkarakter melalui Literasi Materi PAI di Sekolah Dasar - Mohammad Soddiq; Trisno Wijoyo; Mohammad Syamsul Arifin (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
Building a generation with character is one of the main goals of education, especially at the elementary school level, as the initial foundation of moral and moral formation. Literacy of Islamic Religious Education (PAI) materials plays an important role in shaping students into individuals who are not only intellectually intelligent, but also have noble personalities. This study aims to explore the role of literacy in building a generation of character through the integration of Islamic values, such as honesty, responsibility, empathy, and tolerance, into students' daily lives. The approach used in PAI learning involves contextual strategies, interactive methods, and the utilization of technology to increase the effectiveness of material delivery. In addition, religious-based extracurricular activities, such as flash pesantren and social actions, also strengthen the internalization of PAI values. The implementation results showed that students who were exposed to PAI literacy consistently experienced improvements in discipline, spiritual awareness, and the ability to be tolerant of others. However, there were some challenges in implementing this literacy, such as limited resources, lack of access to technology and lack of parental involvement. This study emphasizes the importance of collaboration between schools, teachers, parents and communities in supporting effective PAI literacy implementation. With an integrated and sustainable approach, PAI literacy materials can become a solid foundation in forming a generation with strong character, noble character, and able to make a positive contribution to the nation and religion.